The Maloca: Sustainable Amazonian Vernacular Architecture - Miranda North, Rossana (2012)
The Maloca is a vernacular construction which is still visible in some Amazonian ethnic groups. It is an expression of vernaculararchitecture, a cultural manifestation of the Peruvian Amazon, built with natural products from the very forest. It is anecological construction; everything is reused, the few elements of soil are left in the Amazon ground to which they integrate and theremains of wood are used to cook their food.The Malocas are a response and adaptation to the climate and territory. The inhabitants build their homes by themselves withoutprofessional advice from architects and engineers responding to basic needs with ancestral techniques.This construction plays an important role as a means of adaptation to the climate and as protection and development of familyactivities. They are simultaneous expressions of a need to survive the strong heat and rain.They are sustainable, as they represent an example of good use of natural resources and recycling that come from the soil. Theyprovide thermal comfort to the user; also, they are functional and eco-efficient.The Malocas are icons of the Amazonian landscape, of impressive rationality in a physical and climatic environment, of rainand sunshine conditions for an ethnic group with limited resources, limited economically, that provide viable and sustainablesolutions.